2022
DOI: 10.1039/d2nr01378a
|View full text |Cite
|
Sign up to set email alerts
|

A plasmon-enhanced fluorescent gold coated novel lipo-polymeric hybrid nanosystem: synthesis, characterization and application for imaging and photothermal therapy of breast cancer

Abstract: This study reports the synthesis and application of a hybrid lipo-polymeric nanosystem (PDPC NPs) for plasmon enhanced flourescence based NIR imaging and photothermal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…In another study, AuNP-liposome nanocomposite (150-200 nm) have been prepared and illustrated a good CT contrast with better signals compared to commercially available AuNP (15 and 40 nm) (Figure 8), and thus proposing a novel approach for cancer imaging [173]. Similarly, the signal from AuNP-liposome nanocomposite was strong and stable inside the tumor after injection, signifying the potential stability and tissue retention of the construct [174,175].…”
Section: Imagingmentioning
confidence: 93%
“…In another study, AuNP-liposome nanocomposite (150-200 nm) have been prepared and illustrated a good CT contrast with better signals compared to commercially available AuNP (15 and 40 nm) (Figure 8), and thus proposing a novel approach for cancer imaging [173]. Similarly, the signal from AuNP-liposome nanocomposite was strong and stable inside the tumor after injection, signifying the potential stability and tissue retention of the construct [174,175].…”
Section: Imagingmentioning
confidence: 93%
“…Appidi et al reported PDPC NPs, a lipo-polymeric hybrid nanoparticles surface coated with Au (PDPC-co-loaded with IR780 (PDPC-IR-Au NPs) with HD d of 94.2 ± 14.9 nm. The nanosystem exhibited plasmon-enhanced fluorescence, demonstrating a heightened intracellular ROS, inducing DNA damage and apoptosis when tested against MCF-7 breast cancer cells 66 .…”
Section: Bio-nanomaterials Used For Pttmentioning
confidence: 99%
“…Prospective nanomaterials employed as smart delivery platforms of distinct biopesticides and development of NBPs. …”
Section: Nanobiopesticides: An Efficient Biodegradable Approach For P...mentioning
confidence: 99%